Determination of lead in commercial mineral water by differential pulse anodic stripping vol tammetry technique - Noor, Suhailey Mohd (Universiti Sains Malaysia, 2006)
Voltammetric determination of lead in commercial mineral water using Differential Pulse Anodic Stripping Voltammetry (DPASV) technique is described. The analysis is carried without any pretreatment and using Britton-Robinson buffer as the supporting electrolyte. The electrodes used in this analysis are hanging mercury dropping electrode (HMDE), which act as the working electrode, a platinum electrode as auxiliary electrode and an Ag/AgKCisat reference electrode, respectively. Optimum voltammetric parameter for the analysis of the samples such as initial potential (E,), final potential (Et), deposition potential (Eacc), deposition time (tacc) and scan rate (v) are determined prior to sample analysis using lead standard solution. Optimum voltammetric condition of analysis, pH of supporting electrolyte is also determined. The detection of lead is carried out at concentration of 15 parts per billion (ppb). The result shows that the optimum voltammetric parameters for the determination of lead in mineral water were, initial potential, ~of -0.7 Volt, final potential, Et of -0.2 Volt, deposition potential, Eacc of -0.7 Volt, deposition time, tacc of 140 seconds and scan rate (v) of 0.020 Volt per second was obtained. The pH 3.0 was found out to be the optimum voltammetric condition for the determination of lead in samples. 15 different samples of mineral water were analyzed in this research project. The results show that for all the samples, lead was not detected. 1